Implementasi Program SADARI pada Siswi Sekolah Menengah Atas di Kota Pontianak - Lidia Hastuti; Sutrisno Sutrisno; Ridha Mardiani; Annisa R; Mardiani Mardiani; Indah Indah; Meisy Meisy (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
AbstractCancer is one of the four major diseases in society. And can attack all walks of life without exception and without knowing social status, age or gender. Children, adolescents, and adults have not escaped this deadly attack. But from the data available most women are affected by cancer. Breast cancer still ranks first in new cases and cancer deaths, amounting to 43.3% and 12.9%. The highest cancer suffered by Indonesian women is breast cancer with an incidence of 26 per 100,000 women. One effort that can be done to prevent breast cancer is to implement a healthy lifestyle and breast self-awareness (BSE). This examination can detect breast cancer early and almost 85% of lumps in a woman's breast are found by the sufferers themselves. The Care for society program aims to improve adolescent reproductive health through BSE examination as a screening for disease. The implementation of BSE program assistance was carried out for high school students (Muhammadiyah I High School) in Pontianak. Presentation of Information to Teachers and School UKS Officers to periodically inform of BSE and provide direct assistance to students in conducting BSE examination. An increase in average knowledge after being given an explanation of breast cancer in students and skills in BSE examination after being given assistance. BSE Assistance by Health Workers and UKS Officers increases students' knowledge and awareness to conduct BSE examination in an effort to prevent breast cancer events.